Maria de Mesquita Pimentel: A nova glória dos Pimentéis no mosteiro de S. Bento de Cásstris - Conde, Antónia Fialho (2022)
On the basis of the analysis of the documentary collection of the monastery of S. Bento de Cástris and intensive archival research, we sought to trace the path of the Cistercian nun in the community she joined, especially in terms of the positions she held, as well as her geographical and family origins. We have also tried to understand her family network and the elites, in cultural and intellectual terms, with whom she might have had contact in the Eborense environment of the late 16th century. // A partir da análise do espólio documental do mosteiro de S. Bento de Cástris e de intensa pesquisa arquivística, procurou desenhar-se o percurso da religiosa cisterciense na comunidade em que ingressou sobretudo em termos dos cargos que desempenhou, bem como traçar as suas origens geográficas e familiares. Procurou-se ainda entender a sua rede familiar e as elites, em termos culturais e intelectuais, com quem poderia ter contacto no ambiente eborense de finais do século XVI.